Programming as learning resource in middle school - Salvador, Ricardo P. (2018)
In this work we study the influence, in the kinematics learning ofsecondary students, of the construction of a simulation using the SqueakEtoysgraphical programming environment. An experimental work was carried outwith two groups of students. One group used an interactive tutorial in whichthey constructed the simulation. The experiment was evaluated using a pretest/ posttestprotocol. The results indicate an increase in students' gradesand interest in programming as a didactic resource, which encouragesdesigning similar activities and exploring this resource in other disciplines.